KETEPATAN SHOOTING FUTSAL MELALUI SELF TALK POSITIF DI SMP NEGERI 2 JAWAI - Tiya Nurhadi; Victor G Simanjuntak; Ahmad Atiq (Universitas Tanjungpura, 2020)
AbstractThe problem in this study is whether there is a positive Selftalk to the accuracy of shooting in futsal extracurricular participants in SMP Negeri 2 Jawai. The purpose of this study was to determine the effect of positive self talk exercises on the accuracy of shooting using the instep in futsal games on futsal extracurricular participants in SMP Negeri 2 Jawai 2019.This type of research used in this study is a quasi experimental design with pretest-posttest control group design. This research has two groups: the experimental group and the control group. The experimental group was treated (treatmet) a positive selftalk exercise method and the control group was not treated. The treatment given by the researchers was 12 meetings with a frequency of 3 times a week for 4 weeks or 1 month. Sampling in this study by using total sampling. The samples in this study were all included because the sample was only 15 people. The instrument in this study was the shooting accuracy test using the instep to the target on the futsal playing field. Data analysis using t test (paired sample t test) at the significance level of 0.05.The results of this study are that there is a significant positive effect of self-talk training on the accuracy of shooting on futsal extracurricular participants in SMP Negeri 2 Jawai. With the value of the experimental group t value (7.966)> t table (1.894), the increase in the percentage of the experimental group was 66.07%, while in the control group the value of tcount (0.956)> ttable (1.943. Results and control group amounted to 5.520% Keywords: Positive self talk exercise, Shooting Accuracy, Futsal